1984
DOI: 10.1126/science.224.4653.1064
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biology of Osmoregulation

Abstract: The drought of 1983 resulted in some 10 billion dollars in agricultural losses and has focused attention on the vulnerability of our major crops to this devastating form of environmental stress. This article is concerned with the molecular biology of a new class of genes, called osm (osmotic tolerance) genes, that protect bacteria like Escherichia coli against osmotic stress and may work in a similar manner in plants and animals. Osm genes govern the production of a class of molecules, such as betaine and prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
337
1
4

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 567 publications
(349 citation statements)
references
References 20 publications
7
337
1
4
Order By: Relevance
“…compatível no citoplasma para neutralizar os efeitos dos sais acumulados no vacúolo (Steward et al, 1974;LeRudulier et al, 1984). O acúmulo de prolina favorece também a hidratação do protoplasma alem de funcionar como reserva, especialmente para a síntese de algumas enzimas específicas (Navari-Izzo et al, 1990;Lima et al, 1997).…”
Section: Resultsunclassified
“…compatível no citoplasma para neutralizar os efeitos dos sais acumulados no vacúolo (Steward et al, 1974;LeRudulier et al, 1984). O acúmulo de prolina favorece também a hidratação do protoplasma alem de funcionar como reserva, especialmente para a síntese de algumas enzimas específicas (Navari-Izzo et al, 1990;Lima et al, 1997).…”
Section: Resultsunclassified
“…Therefore, media and growth conditions applied to P. rosea were tested with few modifications on the strains listed in Table 1. As a rule, we had first screened media known to support biomass production of our strains (data not shown) added with 1 g l -1 agar, and then we supplemented the best medium for each strain with appropriate concentrations of sucrose and proline (the latter acting as an osmo-protectant 25 ). The addition of sucrose and proline favored adaptation to the components of the hypertonic buffer (P medium) used for the subsequent cell wall digestion and for protoplast production.…”
Section: Growth Of the Strains And Protoplast Productionmentioning
confidence: 99%
“…Several reports have shown that osmoprotectors, such as betaine and proline, allow the bacteria to support higher concentrations of sodium chloride (Le Rudulier and Bouillard 1983;Le Rudulier et al 1984). Knochel (1990) observed a high correlation between the optimal growth temperature of several Aeromonas spp.…”
Section: -----------------------------------------------------mentioning
confidence: 99%
“…adaptation of bacterial cells to high sodium chloride concentrations has been associated with modification of the circulation of sodium ions across the membrane (Le Rudulier et al 1984). Several reports have shown that osmoprotectors, such as betaine and proline, allow the bacteria to support higher concentrations of sodium chloride (Le Rudulier and Bouillard 1983;Le Rudulier et al 1984).…”
Section: -----------------------------------------------------mentioning
confidence: 99%